Case Report: melanoma and melanocytic nevus differentiation with reflectance confocal microscopy. - Łudzik, Joanna (F1000Res, 2015)
Historically, melanoma has been typically diagnosed by naked-eye examination and confirmed with invasive biopsy. However, recently the use of reflectance confocal microscopy enables non-invasive bedside diagnosis of clinically equivocal lesions. We present a case in which reflectance confocal microscopy was used to evaluate two skin lesions in the same patient confirming the diagnosis of a melanoma and potentially avoiding invasive biopsy in the second benign melanocytic lesion.  Clinicians should be aware of the availability of new non-invasive technologies that can aid in early diagnosis of malignant skin tumors and potentially reduce the number of benign lesion excisions.